Financial data and the skewed generalized t distribution - Theodossiou, Panayiotis (My University, 1998)
This paper develops a skewed extension of the generalized t (GT) distribution, introduced by McDonald and Newey (1988). In particular, the paper derives the mathematical moments and other properties of the distribution and assesses its ability to fit the empirical distribution of several financial series characterized by skewness and excess kurtosis. In all cases the skewed GT provides an excellent fit to the empirical distribution of data
Keywords: Management science; Finance; Value at risk; Risk management; Data reduction; Mathematical models